Sex in aging matters: exercise and chronic stress differentially impact females and males across the lifespan - Sullens, D. Gregory; Gilley, Kayla; Moraglia, Luke E.; Dison, Sarah; Hoffman, Jessica T.; Wiffler, Madison B.; Barnes, Robert C.; Ginty, Annie T.; Sekeres, Melanie J. (Frontiers in Aging Neuroscience, 2025)
Assessing sex as a biological variable is critical to determining the influence of environmental and lifestyle risks and protective factors mediating behavior and neuroplasticity across the lifespan. We investigated sex differences in affective behavior, memory, and hippocampal neurogenesis following short- or long-term exposure to exercise or chronic mild stress in young and aged mice. Male and female mice were assigned control, running, or chronic stress rearing conditions for 1 month (young) or for 15 months (aged), then underwent a behavioral test battery to assess activity, affective behavior, and memory. Stress exposure into late-adulthood increased hyperactivity in both sexes, and enhanced anxiety-like and depressive-like behavior in aged female, but not male, mice. One month of stress or running had no differential effects on behavior in young males and females. Running increased survival of BrdU-labelled hippocampal cells in both young and aged mice, and enhanced spatial memory in aged mice. These findings highlight the importance of considering sex when determining how aging is differently impacted by modifiable lifestyle factors across the lifespan.